2021
DOI: 10.1037/sgd0000476
|View full text |Cite
|
Sign up to set email alerts
|

A commentary on COVID-19 and the LGBT community in Nigeria: Risks and resilience.

Abstract: Since the onset of the Coronavirus disease 2019 (COVID-19) pandemic, there has been substantial research and information in media about the mechanisms, and health and economic impacts of COVID-19. There is, however, less information about the possible consequences of this stressful period in developing countries, such as in sub-Saharan Africa; and even less so among lesbian, gay, bisexual, and transgender (LGBT) individuals in these regions. In this commentary, we briefly describe the consequences of the COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Nevertheless, structural levels were also influenced by individual commitments. In this sense, online meetings and online communities potentially increased the visibility of marginalized groups and influenced policies and structural vulnerability, as shown in a Nigerian article ( Oginni et al, 2021 ). Online presence was connected to less risk and exposure because of not meeting face-to-face.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, structural levels were also influenced by individual commitments. In this sense, online meetings and online communities potentially increased the visibility of marginalized groups and influenced policies and structural vulnerability, as shown in a Nigerian article ( Oginni et al, 2021 ). Online presence was connected to less risk and exposure because of not meeting face-to-face.…”
Section: Resultsmentioning
confidence: 99%
“…Online presence was connected to less risk and exposure because of not meeting face-to-face. Additionally, online meetings had a wider range for meeting with others and increasing the visibility of adversities or harm ( Oginni et al, 2021 ). Thus, individual and community engagements were impacting structures and reduced vulnerability at a structural level.…”
Section: Resultsmentioning
confidence: 99%
“…To date, a few published studies have explored the impact of the COVID-19 pandemic on LGBTQ individuals. Scholarship has explored the impact of COVID-19 on LGBT people in Chile (Barrientos et al, 2021) and Nigeria (Oginni et al, 2021), how LGBT youth and emerging adults found support during the COVID-19 pandemic (Fish et al, 2020; Woznicki et al, 2020), LGBTQ palliative care during the COVID-19 pandemic (Rosa et al, 2020), mental health needs and psychological distress of LGBT youth and college students (Gonzales et al, 2020; Gilbert et al, 2020; Hawke et al, 2021; Hunt et al, 2021), the role of internalized stigma in predicting protective health behaviors (Solomon et al, 2021), the perceived threat of COVID-19 with sexual minority women (Potter et al, 2020), and sleep disturbances of sexual minority men during the COVID-19 pandemic (Millar et al, 2020).…”
Section: Lgbtq Minority Stress and Resiliencementioning
confidence: 99%
“…ECAs face different forms of disadvantages in academia based on intersecting characteristics, such as gender, race, age, childcare and other caring roles, disability, reproductive labour, income, and nationality (Thwaites and Pressland 2016;Bosanquet 2017;Caretta et al 2018;Bono, De Craene, and Kenis 2019;Webster and Caretta 2019; Briscoe-Palmer and Mattocks 2020; Hughes 2021). On top of this, students and staff from marginalised communities have also been disproportionately hit by COVID-19: from the health inequalities experienced by racialised minorities (Anyane-Yeboa, Sato, and Sakuraba 2020), to the uneven impact of isolation on migrants and LGBT+ communities (Chen et al 2020;Oginni, Okanlawon, and Ogunbajo 2021). The unfolding financial impacts of the pandemic are having disproportionate effects on the most precarious workers (Woolston 2020b(Woolston , 2020c.…”
Section: Hierarchical Structuresmentioning
confidence: 99%